(untitled) (La U Investiga, 2021)
Simulation within the teaching process of health professionals, manages to reduce the distance between students and professional activities related to clinical care, being the Briefing and Debriefing tool used in clinical simulation for students of Health Sciences, with This premise, a scientific investigation was developed with the following objective: Determine the usefulness of briefing and debriefing as a tool in clinical simulation for Health Sciences Students. A descriptive review was carried out, analyzing a search in electronic databases. It has been of great importance to collect from the state of the art, on the documental research in a systemized way, giving, as a result, a deeper analysis which contributes to the study topic of those aspects related to these tools in learning environments aspects related to these tools in learning environments, where teachers and students act together who must reconsider and deliberate why they make certain decisions, evaluating their actions individually, as well as your act on the team. The usefulness of the briefing and debriefing was defined as part of the clinical simulation to achieve competencies and skills in Health Sciences students, a reason that encourages thinking about developing training programs for teachers and students as a methodology that facilitates the correction of possible errors that reduce the effectiveness of this process.